Study of stability and antifragility of reputation in view of multi-vector character of reputation management of enterprises - Derevianko, О.Н.; Дерев’янко, Олена Георгіївна (My University, 2017)
The paper is devoted to the development of fundamental bases of the reputation management of enterprises and elaboration of its methodological and methodical support. There was offered to use “antifragility” conception in the reputation management of an enterprise that allows to activate the cooperation with key stakeholders and to trace the effectiveness of managerial arrangements. At that reputation antifragility that is the ability to its self-support is a criterion of effectiveness of the reputation management of an enterprise. The projection of Taleb’s conception on the reputation management of enterprises provides the management balance (as a purposeful formation of an enterprise reputation) and self-management balance (as a spontaneous formation of an enterprise reputation) at the conceptual level. At that in the aspect of the economic approach, “antifragility of an enterprise reputation” is not equal to the notion “anticrisis enterprise management”, where the last one reproduces the process of counteraction to crisis phenomena. The features of reputation antifragility are considered as: stability as a closest synonym of antifragility; while assessing a reputation, it is necessary to take into account its ability to resist rare destructive events; anticrisis (crisis) reputation management as a necessary but not enough method of providing antifragility of an enterprise reputation; informational transparency and its necessity to form an antifragile enterprise reputation.
Keywords: management decentralization; stakeholders; economic interpretation of Taleb antifragility conception; comparative assessment of stability and antifragility; business informational transparency